2021
DOI: 10.1186/s12935-021-02198-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast double-hit lymphoma management and outcomes: a real-world multicentre experience

Abstract: Background Primary breast double-hit lymphoma (PB-DHL) is a rare, highly aggressive malignancy that poses challenges regarding accurate diagnosis and selecting optimal treatment regimens. Methods We retrospectively reviewed 48 cases of patients diagnosed with PB-DHL in six academic centres between June 2014 and June 2020 in China. Study-specific data were recorded, including treatment options, therapeutic evaluation, prognostic factors and relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Oki et al OS after first progression was poor even after salvage stem cell transplant (SCT) (3yOS 15% vs. 7%). Albeit, SCT is an option for the treatment of DLBCL with MYC and BCL2 rearrangement, with same prognosis if done after first complete remission or after a second line of treatment with complete response [2] and less CNS progression (p < 0.001). So SCT is generally recommended to reduce CNS relapse rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oki et al OS after first progression was poor even after salvage stem cell transplant (SCT) (3yOS 15% vs. 7%). Albeit, SCT is an option for the treatment of DLBCL with MYC and BCL2 rearrangement, with same prognosis if done after first complete remission or after a second line of treatment with complete response [2] and less CNS progression (p < 0.001). So SCT is generally recommended to reduce CNS relapse rate.…”
Section: Discussionmentioning
confidence: 99%
“…Primary breast lymphoma represents 1% of non-Hodgkin lymphomas and 2% of all extra nodal lymphomas [1]. The most common histologic type is diffuse large B-cell lymphoma (DLBCL) representing 60-85% of cases, followed by marginal zone lymphoma in 16% of cases and follicular lymphoma in 5.4% of cases with rare cases of Burkitt's lymphoma and Hodgkin lymphoma described in the literature [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective Surveillance, Epidemiology, and End Results (SEER) database analysis demonstrated that patients treated with systemic regimens including rituximab followed by radiation therapy had a significantly greater five-year overall survival (OS) compared to those that did not receive radiotherapy [ 12 ]. A retrospective analysis on a limited number of patients demonstrated that treatment with dose-adjusted EPOCH-rituximab, alternating with high-dose methotrexate and cytarabine had a higher five-year OS compared to two other regimens [ 14 ]. Presently, no definitive guidelines exist for primary breast DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing the relevant literature, we found the present clinical issue, that the prognostic value of IPI in PBL is controversial. Studies by Ryan et al [ 6 ], Hu et al [ 9 ], Zhang et al [ 34 ], Shao et al [ 15 ], Yhim et al [ 35 ] demonstrated that the IPI scores were independent risk factors for PFS and OS, while results from Zhao et al [ 36 ], Qu et al [ 37 ] and Zhang et al [ 38 ] confirmed that the IPI scores were not associated with PFS and OS in PBL. The result was presented in the forest graph format (Fig.…”
Section: Discussionmentioning
confidence: 99%